2015
DOI: 10.4238/2015.january.15.15
|View full text |Cite
|
Sign up to set email alerts
|

imDC: an ensemble learning method for imbalanced classification with miRNA data

Abstract: ABSTRACT. Imbalances typically exist in bioinformatics and are also common in other areas. A drawback of traditional machine learning methods is the relatively little attention given to small sample classification. Thus, we developed imDC, which uses an ensemble learning concept in combination with weights and sample misclassification information to effectively classify imbalanced data. Our method showed better results when compared to other algorithms with UCI machine learning datasets and microRNA data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 6 publications
(6 reference statements)
1
33
0
Order By: Relevance
“…Therefore, we concluded that smooth muscle cell apoptosis in coronary heart disease rats was mediated by the mitochondrial pathway. This was also in agreement with the results of previous studies (Chen et al, 2015;Femminella et al, 2015;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, we concluded that smooth muscle cell apoptosis in coronary heart disease rats was mediated by the mitochondrial pathway. This was also in agreement with the results of previous studies (Chen et al, 2015;Femminella et al, 2015;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…miRNA modulate various biological functions, such as cell proliferation, growth, apoptosis, and signal transduction (Chen et al, 2015;Femminella et al, 2015;Higuchi et al, 2015;Wang et al, 2015). Previous studies have also reported that miRNA-146a mediates cellular growth and proliferation in various cells (Alexandrov et al, 2014;Xie et al, 2014;Gu et al, 2015;Hill et al, 2015;Tang et al, 2015;Zhou et al, 2015), however, the role of miRNA-146a in coronary heart disease remains to be elucidated.…”
Section: Introductionmentioning
confidence: 98%
“…In our future work, we will try other features considering long range sequence information, which is indicted to be useful for the enhancer classification in our current work. We will also try the imbalanced classifiers [52][53][54][55][56]on our dataset, which has been employed CD-HIT and random sampling strategy for the large negative data. Combined with some more sophisticated machine learning models and feature reduction methods [57], we anticipate better performance can be achieved.…”
Section: Resultsmentioning
confidence: 99%
“…However, this metric might unsuitable to measure the performance of imbalanced class distribution. Hence, additional metrics like precision, recall, F-measure were used (Wang et al, 2015;Zhang et al, 2015). The experiment was done under two conditions; using all extracted features (FS1) and using reduced features (FS2).…”
Section: Resultsmentioning
confidence: 99%